Role of Adipokines and Other Inflammatory Mediators in Gestational Diabetes Mellitus and Previous Gestational Diabetes Mellitus - Nikolaos Vrachnis; Panagiotis Belitsos; Stavros Sifakis; Konstantinos Dafopoulos; Charalambos Siristatidis; Kalliopi I. Pappa; Zoe Iliodromiti (International Journal of Endocrinology)
Previous Gestational Diabetes Mellitus (pGDM) is a common condition and has been associated with future development of Type 2 Diabetes Mellitus (T2DM) and Metabolic Syndrome (MS) in women affected. The pathogenesis and risk factors implicated in the development of these conditions later in the lives of women with pGDM are not as yet fully understood. Research has recently focused on a group of substances produced mainly by adipose tissue called adipokines, this group including, among others, adiponectin, leptin, Retinol-Binding Protein-4 (RBP-4), and resistin. These substances as well as other inflammatory mediators (CRP, IL-6, PAI-1, TNF-α) seem to play an important role in glucose tolerance and insulin sensitivity dysregulation in women with pGDM. We summarize the data available on the role of these molecules.